Closing a chapter? A protocol for a longitudinal mixed methods study on retirement from elite sport - Ronkainen, N. J.; Schmid, M. J.; Hlasová, H.; Örencik, M.; Schmid, J.; Conzelmann, A. (BMC Psychology, 2023)
Retirement from elite sport represents a major life transition for athletes and requires them to redefine their central life projects, identities, and perhaps even sources of meaning in life. Although an extensive body of literature has identified risk and protective factors in career termination, little is known about the more subjective processes and individual pathways of athletes as they establish their new relationship with work-life and sport. The planned longitudinal mixed methods study follows Swiss elite athletes` transition with a focus on understanding (1) the relationship between psychological resources, life situations at the end of the sports career, and the retirement process; (2) how athletes` post-retirement vocational careers interact with their subjective careers and sense of meaningful work; (3) how athletes reconstruct their identities and relationship with sport over time; and (4) how gender shapes athletes` pathways and reorientation of their life design.